2012
DOI: 10.1371/journal.pone.0041313
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin Inhibits Poly(A)-Tail Synthesis in Nuclear mRNA that Contains AU-Rich Elements by Interacting with Poly(A)-Binding Protein Nuclear 1

Abstract: Background Tristetraprolin binds mRNA AU-rich elements and thereby facilitates the destabilization of mature mRNA in the cytosol. Methodology/Principal Findings To understand how tristetraprolin mechanistically functions, we biopanned with a phage-display library for proteins that interact with tristetraprolin and retrieved, among others, a fragment of poly(A)-binding protein nuclear 1, which assists in the 3'-polyadenylation of mRNA by binding to immature poly(A) tails… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…In yeast, Cth2 has been shown to modulate the selection of the poly(A) site of several mRNAs [46]. More recently, studies have shown that TIS11B regulates the 3’ end processing of the Dll4 mRNA [47], and that TTP could play a role in the polyadenylation of ARE-containing mRNAs via its interaction with poly(A)-binding protein nuclear 1 [48]. It will be of interest to determine whether dTIS11 also participates in nuclear processes and to establish how the Transportin/TIS11 interaction is modulated to intervene in the various roles of TIS11 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, Cth2 has been shown to modulate the selection of the poly(A) site of several mRNAs [46]. More recently, studies have shown that TIS11B regulates the 3’ end processing of the Dll4 mRNA [47], and that TTP could play a role in the polyadenylation of ARE-containing mRNAs via its interaction with poly(A)-binding protein nuclear 1 [48]. It will be of interest to determine whether dTIS11 also participates in nuclear processes and to establish how the Transportin/TIS11 interaction is modulated to intervene in the various roles of TIS11 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…AREs and GREs have been demonstrated to induce rapid deadenylation and subsequent decay of mRNAs, which may be mediated by recruitment of the exosome [68] or 5′-3′ decay machinery [27]. The two classes of 3′ UTR elements serve as binding sites for a multitude of AU-binding proteins (AUBPs) or GU-binding proteins, which can enhance or prevent mRNA decay, in some cases specifically via interaction with the poly(A) tail [65,69,70]. …”
Section: Sequences That Control Poly(a) Tail Lengthmentioning
confidence: 99%
“…Tristetraprolin (TTP) is notorious for promoting cytoplasmic decay of mRNAs containing AREs, but in the nucleus it can directly interact with PABN1 and PAP to inhibit polyadenylation, potentially contributing to a decrease in nuclear export of mRNAs [70,88]. The Hu proteins, which stabilize mRNAs in the cytoplasm, interact with CstF and CPSF during transcriptional 3′ end processing to prevent polyadenylation at poly(A) sites containing U-rich sequences [89].…”
Section: Nuclear Factors That Regulate the Poly(a) Tailmentioning
confidence: 99%
“…A good candidate for the regulation of the initial poly(A) tails size of serum response mRNAs is Zfp36 (tristetraprolin), a protein that is known to bind the AU rich elements that are common in serum response mRNAs and regulates their stability in the cytoplasm [15]. Zpf36 has also been shown to interact with Pabpn1 and inhibit nuclear polyadenylation [47]. In addition, U rich element binding proteins from the Elavl (Hu) family have been shown to affect the addition of the poly(A) tail in vitro [48] and Actb1 mRNA has extensive binding sites for this protein in its 3' UTR [49].…”
Section: Discussionmentioning
confidence: 99%